2019
DOI: 10.3171/2019.4.spine18915
|View full text |Cite
|
Sign up to set email alerts
|

State of the union: a review of lumbar fusion indications and techniques for degenerative spine disease

Abstract: Lumbar fusion is an accepted and effective technique for the treatment of lumbar degenerative disease. The practice has evolved continually since Albee and Hibbs independently reported the first cases in 1913, and advancements in both technique and patient selection continue through the present day. Clinical and radiological indications for surgery have been tested in trials, and other diagnostic modalities have developed and been studied. Fusion practices have also advanced; instrumentation, surgical approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 158 publications
(88 reference statements)
0
72
1
Order By: Relevance
“…However, the literature regarding fusions for lumbar discectomy patients remains controversial with significant variation in clinical practice. 10 Several studies have reported the inefficacy of an additional fusion in improving functional outcomes compared with discectomy alone. [11][12][13][14] Our study attempts to identify ingrained practice pattern biases that exist amongst surgeons performing isolated discectomies versus discectomy and fusion for management of lumbar disc herniation with radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature regarding fusions for lumbar discectomy patients remains controversial with significant variation in clinical practice. 10 Several studies have reported the inefficacy of an additional fusion in improving functional outcomes compared with discectomy alone. [11][12][13][14] Our study attempts to identify ingrained practice pattern biases that exist amongst surgeons performing isolated discectomies versus discectomy and fusion for management of lumbar disc herniation with radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial mapping and recognition of the physical environment is a crucial difference between augmented reality and other navigations systems using conventional display methods. Projecting the required information directly into the line-of sight of the surgeon is considered the natural progression of these well-established methods mitigating the errors associated with attention shift by directly projecting the navigation guidance onto the surgical field [ 22 , 23 ]. Incekara et al evaluated the same AR headset for pre-operative planning of neurosurgical tumor resection in 25 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect an aging population, but also an improvement in the diagnostic process, intraoperative technologies (like spinal navigation) and perioperative care of these patients. However, while a clear benefit in terms of pain, disability and return to work has been shown in patients suffering from spinal instability [ 46 – 48 ], recent RCT’s [ 47 , 49 ] have questioned the usefulness of spinal fusion procedures for other conditions like spinal stenosis or degenerative spondylolisthesis. As a matter of fact, in many situations and in many health systems, decision-making regarding indications for spinal fusion is driven by surgeons’ and patients’ preferences, hospital factors and reimbursement policies [ 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%